Dithienylethenes containing aromatic carbons: Synthesis, photochromism and anion recognition. (April 2015) - Liu, Wenju; Hu, Fang; Chen, Zhiming; Li, Ziyong; Yin, Jun; Yu, Guang-Ao; Liu, Sheng Hua
Abstract: A series of novel dithienylethenes with different aromatic carbons were efficiently synthesized using a four-component Ugi reaction and their structures confirmed by NMR spectroscopy, mass spectroscopy (MS) and elemental analysis. Their photochromic properties and fluorescence behaviors have been measured upon irradiation with UV light in solution. Investigations on their photochromic properties indicated that the dithienylethene derivatives had good reversibility upon irradiation with UV or visible light. In addition, they displayed excellent fluorescence switchable behavior. It was found that the degree of conjugation in the aromatic ring had a great effect on their photochromism and fluorescence properties. Moreover, the anthracene-based dithienylethene derivatives displayed high selectivity towards iodide and the pyrene-based dithienylethenes derivatives could act as a colorimetric fluoride sensor. Graphical abstract: A series of novel dithienylethenes with different aromatic carbons were efficiently synthesized using a four-component Ugi reaction. The dithienylethene derivatives exhibited photochromism, fluorescence switchable behavior and high selectivity towards iodide or fluoride. Highlights: Some dithienylethenes with different aromatic carbons were efficiently synthesized using a four-component Ugi reaction. The dithienylethene derivatives exhibited photochromism and fluorescence switchable behavior. The anthracene or pyrene-based dithienylethene derivatives exhibited high selectivity towards iodide or fluoride.